2019
DOI: 10.1136/bmjsem-2018-000486
|View full text |Cite
|
Sign up to set email alerts
|

Two-peaked increase of serum myosin heavy chain-α after triathlon suggests heart muscle cell death

Abstract: ObjectiveIt has been suggested that the mechanism behind cardiac troponin elevation after strenuous exercise is passage through a cell membrane with changed permeability rather than myocardial cell death. We hypothesised that an increase of cardiac specific myosin heavy chain-alpha (MHC-α; 224 kDa compared with cardiac troponin T’s (cTnT) 37 kDa) could hardly be explained by passage through a cell membrane.MethodsBlood samples were collected from 56 athletes (15 female, age 42.5±9.7, range 24–70 years) before,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The findings of greatest clinical interest are those in WBC, CRP, AST, CK and NT-proBNP because the results would indicate pathology in the resting state in a medical examination [22][23][24][25][26]. This is in line with previous studies on Ironman distance triathlons [7][8][9].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The findings of greatest clinical interest are those in WBC, CRP, AST, CK and NT-proBNP because the results would indicate pathology in the resting state in a medical examination [22][23][24][25][26]. This is in line with previous studies on Ironman distance triathlons [7][8][9].…”
Section: Discussionsupporting
confidence: 80%
“…Norseman (8 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] mg/L, p < 0.001) with a clinically significant increase the following day (39 mg/L, p < 0.001 compared to baseline, < 0.001 compared to finish line). AST had increased at the finish line (99 [74-136] U/L, p < 0.001) but it increased to even higher values the day after the race (142 [99-191] U/L, p < 0.001 compared to baseline, p < 0.05 compared to finish line).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The absence of an association between aerobic capacity and markers for cardiac muscle damage was surprising given the well know cardio-protective health effects of having a high aerobic fitness. We have previously reported that nearly all of the athletes showed pathological values of cTnT (98%) and NT-proBNP (89%) after finishing the race 16 but the clinical value of these observations are under debate. The debate centers on whether the elevated biomarkers seen after ultra-endurance races reflect true pathological changes or if they are a part of the normal physiological response 17,18 .…”
Section: Discussionmentioning
confidence: 99%